무선 통신 시스템에서 다중 안테나 기반의 프리코딩 방법 및 장치 - LEE JAEWON; LEE SEUNGHYUN; HAN MINSIG; KANG CHUNGGU; LEE HYOJIN (2023)
본 개시는 LTE와 같은 4G 통신 시스템 이후 보다 높은 데이터 전송률을 지원하기 위한 5G 또는 6G 통신 시스템에 관련된 것이다. 본 개시의 일 실시예에 따르면, 통신 시스템에서 네트워크 엔티티(network entity)의 방법이 제공된다. 네트워크 엔티티의 방법은, 적어도 하나의 단말을 서빙 하는 제1 그룹에 포함된 복수의 제1 TP(transmission point) 및 제2 그룹에 포함된 복수의 제2 TP 간 비율을 조절하기 위한 스케줄링의 수행 여부를 결정하는 단계; 상기 스케줄링을 수행할 것으로 결정하는 경우, 상기 적어도 하나의 단말과 연관된 정보에 기반하여 상기 복수의 제2 TP 중 적어도 하나의 제2 TP를 제1 TP로 전환할지 여부를 결정하는 단계; 상기 적어도 하나의 제2 TP를 상기 제1 TP로 전환할 것으로 결정되는 경우, 상기 적어도 하나의 제2 TP에 상기 제1 TP로 동작할 것을 지시하는 지시자를 전송하는 단계를 포함하며, 상기 제1 TP로 동작하는 경우, 상기 네트워크 엔티티에서 신호에 대한 프리코딩(precoding)이 수행되고, 상기 제2 TP로 동작하는 경우, 상기 제2 TP에서 신호에 대한 프리코딩이 수행되는 것을 특징으로 한다. 이에 따르면, 다수의 TP들을 제어하는 CPU가 허용할 수 있는 계산 복잡도 및 프론트 홀 용량이 제한된 환경에서 보다 향상된 서비스를 제공할 수 있다. The present disclosure relates to a 5G or 6G communication system for supporting a data transmission rate higher than that of a 4G communication system, such as LTE. According to one embodiment of the present disclosure, a method of a network entity in a communication system is provided. The method of a network entity comprises steps of: determining whether to perform scheduling for adjusting the ratio between a plurality of first transmission points (TPs) included in a first group serving at least one terminal and a plurality of second TPs included in a second group; determining whether to convert at least one from among the plurality of second TPs into a first TP on the basis of information associated with the at least one terminal, if performance of the scheduling has been determined; and transmitting, to the at least one second TP, an indicator indicating an operation with the first TP, if conversion of the at least one second TP into the first TP has been determined, wherein, if operating occurs with the first TP, signals are precoded in the network entity, and if operating occurs with the second TP, signals are precoded in the second TP. Therefore, an improved service can be provided in an environment where computational complexity, which can be permitted by a CPU controlling multiple TPs, and the fronthaul capacity are limited.